Critical role for IL-4 in the development of transplant arteriosclerosis in the absence of CD40-CD154 costimulation. - Ensminger, S; Spriewald, B; Sorensen, H; Witzke, O; Flashman, E; Bushell, A; Morris, P; Rose, M; Rahemtulla, A; Wood, K (2001)
Blockade of the CD40-CD154 pathway can inhibit CD4(+) T cell activation but is unable to prevent immune responses mediated by CD8(+) T cells. However, even in the absence of CD8(+) T cells, inhibition of the CD40-CD154 pathway is insufficient to prevent the development of transplant arteriosclerosis. This study investigated the mechanisms of transplant arteriosclerosis in the absence of the CD40 pathway. C57BL/6 CD40(-/-) (H2(b)) recipients were transplanted with MHC-mismatched BALB/c (H2(d)) aortas. Transplant arteriosclerosis was evident in both CD40(-/-) and CD40(+/-) mice (intimal proliferation was 59 +/- 5% for CD40(-/-) mice vs 58 +/- 4% for CD40(+/-) mice) in the presence or absence of CD8(+) T cells (intimal proliferation was 46 +/- 7% for CD40(-/-) anti-CD8-treated mice vs 50 +/- 10% for CD40(+/-) anti-CD8-treated mice), confirming that CD8(+) T cells are not essential effector cells for the development of this disease. In CD40(-/-) recipients depleted of CD8(+) T cells, the number of eosinophils infiltrating the graft was markedly increased (109 +/- 24 eosinophils/grid for CD40(-/-) anti-CD8-treated mice vs 28 +/- 7 for CD40(+/-) anti-CD8-treated mice). The increased presence of eosinophils correlated with augmented intragraft production of IL-4. To test the hypothesis that IL-4 was responsible for the intimal proliferation, CD8 T cell-depleted CD40(-/-) recipients were treated with anti-IL-4 mAb. This resulted in significantly reduced eosinophil infiltration into the graft (12 +/- 5 eosinophils/grid for CD40(-/-) anti-CD8(+), anti-IL-4-treated mice vs 109 +/- 24 for CD40(-/-) anti-CD8-treated mice), intragraft eotaxin, CCR3 mRNA production, and the level of intimal proliferation (18 +/- 5% for CD40(-/-) anti-CD8(+)-, anti-IL-4-treated mice vs 46 +/- 7% for CD40(-/-) anti-CD8-treated mice). In conclusion, elevated intragraft IL-4 production results in an eosinophil infiltrate and is an important mechanism for CD8(+) T cell-independent transplant arteriosclerosis in the absence of CD40-CD154 costimulation.